Modelling net photosynthesis rate of field grown cocksfoot leaves under different nitrogen, water and temperature regimes - Peri, Pablo Luis (2002)
A simple multiplicative model using temperature, foliage nitrogen (N) concentration and water status was developed to predict the maximum photosynthetic rate (Pmax) of field-grown cocksfoot (Dactylis glomerata L.) leaves when none, one, two or all the factors were limiting. The highest Pmax was 27Æ4 lmol CO2 m–2 s)1 in non-limited conditions, which was defined as the standardized Pmax value dimensionless (Pmaxs ¼ 1). Pmax s increased 0Æ058 units per °C from 10°C to the optimum range (19–23°C) (Pmaxs ¼ 1) and then declined 0Æ077 units of Pmaxs per °C from 23 to 31°C. Pmax s ¼ 1 was also measured from 59 to 52 g N kg)1 dry matter (DM) foliage N. Pmaxs then decreased at the rate of 0Æ115 units per 10 g N kg)1 DM from 52 to 26 g N kg)1 DM, and 0Æ409 units of Pmaxs per 10 g N kg)1 DM from 26 to 15 g N kg)1 DM. For predawn leaf water potential (wlp), Pmaxs ¼ 1 was measured from )0Æ1 to )1Æ2 bar but declined linearly at a rate of 0Æ078 units per bar of wlp from )1Æ2 to )14Æ0 bar because of a linear decrease in stomatal conductance. An interaction between low N content (£20 g N kg)1 DM) and high temperature (>23°C) was also detected. Together, this multiplicative model accounted for 0Æ82 of the variation in Pmaxs.